(untitled) (Bulletin KNOB, 2022)
The new premises of the Dutch Colonial Office (Departement van Koloniën) on the Plein in The Hague, built between 1859 and 1861 to a design by the Chief National Architect, Willem Nicolaas Rose (1801-1877), is an early and important attempt to deal with thermal comfort and indoor climate in buildings in the Netherlands. The heating and ventilation of buildings garnered a lot of attention in the nineteenth century, sparked by new ideas about health and thermal comfort and related technical advances. Many public buildings had high occupancy levels, often resulting in deplorable air quality. Controlling the indoor temperature was another complex issue. In 1858, Rose was appointed Chief National Architect with responsibility for all government buildings. In his design for the Colonial Office he experimented with modern materials and techniques including iron, cavity walls, large glazed surfaces and mechanical installations for heating and ventilation. He also exerted considerable influence on Dutch architecture through his flexible approach to the spatial layout of buildings, the use of classical visual language and the introduction of the Rundbogenstil (round-arch style). His Colonial Office building consequently differed markedly from the existing buildings in and around the Binnenhof. However, his unbridled belief in progress and highly individual evaluation of historical buildings also attracted fierce criticism. To heat and ventilate the Colonial Office Rose made use of the Van Hecke system. This entailed an extensive network of ducts through which fresh, warm air was dispersed throughout the building from the ground floor heating chambers with the help of ventilators. But the mechanical services were just a small part of the overall climate system: various architectural and structural strategies were an integral part of the system. During the very first winter it became clear that the climate system was not up to the job of heating and ventilating the various rooms adequately. Owing to the many problems that arose, the mechanical systems were transferred in 1862 to the Tehuis voor Oud-Militairen Bronbeek near Arnhem, also designed by Rose. But although the system in the Colonial Office building did not operate as required, the design itself was very important for the development of climatic systems in the nineteenth century. In the absence of scientific knowledge and calculation models, the development of knowhow depended very much on real-life experiments, and there were very few of these in the middle of the nineteenth century in the Netherlands. As such, the Colonial Office building can be seen an early and important example of a climate control design that genuinely attempted to integrate mechanical systems for heating and ventilation with the design of the building.